2021
DOI: 10.1177/23328584211060804
|View full text |Cite
|
Sign up to set email alerts
|

Does Diagnostic Feedback Promote Learning? Evidence From a Longitudinal Cognitive Diagnostic Assessment

Abstract: Assessment for learning emphasizes the importance of feedback to promote learning. To explore whether cognitive diagnostic feedback (CDF) promotes learning and whether it is more effective than traditional feedback in promoting learning, this study conducted a quasi-experiment by utilizing a longitudinal cognitive diagnostic assessment to compare the effect of three feedback modes on promoting learning, including CDF, correct–incorrect response feedback (CIRF), and no feedback. The results provided some eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 56 publications
0
21
0
3
Order By: Relevance
“…The empirical research findings showed promise that teachers and students can use feedback from these models to decide next steps in learning in different learning domains, such as reading (e.g., Kim, 2015 ), listening (e.g., Min and He, 2022 ), writing (e.g., Xie, 2017 ), and mathematics (e.g., Wu, 2019 ). Tang and Zhan (2021) also showed that CDM promotes students’ learning. However, CDMs have not been applied to the energy domain to characterize or support students’ learning.…”
Section: Introductionmentioning
confidence: 90%
“…The empirical research findings showed promise that teachers and students can use feedback from these models to decide next steps in learning in different learning domains, such as reading (e.g., Kim, 2015 ), listening (e.g., Min and He, 2022 ), writing (e.g., Xie, 2017 ), and mathematics (e.g., Wu, 2019 ). Tang and Zhan (2021) also showed that CDM promotes students’ learning. However, CDMs have not been applied to the energy domain to characterize or support students’ learning.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, traditional assessments do not have the contextual affordance of reflecting on HOTS levels for skill diagnosis. On the contrary, detailed cognitive modeling in comprehension is parallel to cognitive diagnostic assessment that can provide each learner's developmental trajectory in reading (Tang and Zhan, 2021). It provides ample systematic information to the teacher and learner about how and where to focus on improvement.…”
Section: Hots-based Reading Comprehensionmentioning
confidence: 99%
“…Because they incorporate additional variables beyond scored item responses, CDMs have the potential to provide richer diagnostic feedback than traditional item response theory (IRT) models (Ma & de la Torre, 2020). Such diagnostic feedback has been examined for its ability to promote students’ learning outcomes (Tang & Zhan, 2021). For example, teachers can use diagnostic feedback to design and improve remedial instruction, with the goal of efficient and targeted teaching interventions for an individual or group of students (e.g., Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the diagnostic results of most existing CDMs cannot fully reflect individual differences in problem-solving behaviors, which may further limit the amount of information contained in the existing diagnostic feedback. A number of studies in the field of learning science have shown that the richer the information contained in the feedback, the more conducive it is to promote student learning (e.g., Dunn et al, 2012; Maddox et al, 2008; Tang & Zhan, 2021).…”
Section: Introductionmentioning
confidence: 99%